Comparative Study to Assess the Knowledge Regarding Newborn Care between Mother and Father in Selected Hospitals of Pune City. - Jogdeo, Bhagyashree; Khumujam, Jeena (International Journal of Nursing Research, 2023)
Children are the future of society, and mother and father are the guardian of that future. Conventionally, the role of mother as a direct caregiver and the role of a father is providing financial support. However, nowadays, both are involved in direct care as well as financial outlook. This new trend accepted by various countries. Father also availing the facility of leave after delivery of newborn. Aim: The aim of the study was to compare the knowledge regarding newborn care between mother and father. Objectives: (1) The objectives of the study were to assess the knowledge regarding newborn care among parents and (2) to associate the findings with selected demographic variables. Materials and Methods: A total of 200 parents were selected as samples by nonprobability convenient sampling technique used to collect the data. Research tool includes Sections I and II. Section I includes demographic variables of parents. Section II consists of a structured questionnaire to assess the knowledge of parents regarding newborn care. The tool was content validated by experts and translated into the local language which was again validated. The reliability value is 0.78, which is high. The analysis was performed using frequency and percentage distribution and Fisher’s exact test. Results: Father and mother have an equal level of knowledge regarding newborn care. A significant association between knowledge and parents age, no of children, and previous knowledge. Mother’s knowledge regarding newborn care significantly associated with her educational status,occupation,source of information,religion,family income. Conclusion: Research findings show that mother and father have average knowledge regarding newborn care. These findings indicate the need for awareness among parents to decrease the infant mortality rate due to malpractice.